Potential Anti-allergic Effects of Bibenzyl Derivatives from Liverworts, Radula perrottetii - Asai, Haruka; Kato, Koichi; Suzuki, Moe; Takahashi, Misato; Miyata, Erika; Aoi, Moeka; Kumazawa, Reika; Nagashima, Fumihiro; Kurosaki, Hiromasa; Aoyagi, Yutaka; Fukuishi, Nobuyuki (Planta Medica, 2022)
The liverwort Radula perrottetii contains various bibenzyl derivatives which are known to possess various biological activities, such as anti-inflammatory effects. Mast cells (MC) play crucial roles in allergic and inflammatory diseases; thus, inhibition of MC activation is pivotal for the treatment of allergic and inflammatory disorders. We investigated the effects of perrottetin D (perD), isolated from Radula perrottetii, and perD diacetate (Ac-perD) on antigen-induced activation of MCs. Bone marrow–derived MCs (BMMCs) were generated from C57BL/6 mice. The degranulation ratio, histamine release, and the interleukin (IL)-4 and leukotriene B4 productions on antigen-triggered BMMC were investigated. Additionally, the effects of the bibenzyls on binding of IgE to FcεRI were observed by flow cytometry, and signal transduction proteins was examined by Western blot. Furthermore, binding of the bibenzyls to the Fyn kinase domain was calculated. At 10 µM, perD decreased the degranulation ratio (p < 0.01), whereas 10 µM Ac-perD down-regulated IL-4 production (p < 0.05) in addition to decreasing the degranulation ratio (p < 0.01). Both compounds tended to decrease histamine release at a concentration of 10 µM. Although 10 µM perD reduced only Syk phosphorylation, 10 µM Ac-perD diminished phosphorylation of Syk, Gab2, PLC-γ, and p38. PerD appeared to selectively bind Fyn, whereas Ac-perD appeared to act as a weak but broad-spectrum inhibitor of kinases, including Fyn. In conclusion, perD and Ac-perD suppressed the phosphorylation of signal transduction molecules downstream of the FcεRI and consequently inhibited degranulation, and/or IL-4 production. These may be beneficial potential lead compounds for the development of novel anti-allergic and anti-inflammatory drugs.
Keywords: liverworts; Radula perrottetii; Radulaceae; mast cells; allergy; inflammation